The role of clinical parapapillary atrophy evaluation in the diagnosis of open angle glaucoma - Joshua R Ehrlich (Dove Medical Press, 2010)
Joshua R Ehrlich, Nathan M RadcliffeDepartment of Ophthalmology, Weill Cornell Medical College, New York, NY, USAPurpose: To determine if clinical evaluation of parapapillary atrophy (PPA) significantly improves the ability to distinguish open-angle glaucoma (OAG) patients from glaucoma suspects.Methods: Patients in this study were under evaluation for glaucoma and had open angles, at least one reliable 24-2 SITA-standard automatic perimetry, and digital stereophotographs of the optic disc. PPA was identified clinically as a parapapillary region of absent (βPPA) or hyper/hypopigmented (αPPA) retinal pigment epithelium. A single masked observer evaluated photos for: vertical cup-to-disc ratio (CDR), clock hours of total and βPPA, βPPA as percentage width of the optic disc, presence or absence of βPPA at each disc quadrant, and ordinal rating of total PPA. Generalized linear models were used to determine odds of an abnormal or borderline glaucoma hemifield test (GHT) as a function of PPA variables and covariates; model fit was assessed using the log-likelihood ratio test.Results: Of 410 consecutive patients, 540 eyes (of 294 patients) met inclusion criteria. Mean age was greater among patients with abnormal compared with normal GHT (P < 0.001), but sex and race/ethnicity did not differ between groups (P ≥ 0.22). Age, central corneal thickness (CCT) and CDR (P ≤ 0.006), but not intraocular pressure (IOP) (P = 0.71), were significant univariable predictors of the odds of an abnormal GHT. All PPA parameters significantly predicted GHT (P ≤ 0.03), except presence of temporal βPPA (P = 0.25). Adjustment for age, CCT, IOP, and CDR reduced the association between PPA and GHT, and model fit was not greatly improved by addition of PPA variables.Conclusions: Addition of most PPA parameters to a model already containing commonly assessed variables including age, CCT, IOP, and CDR does not significantly improve the ability to distinguish OAG patients from glaucoma suspects.Keywords: glaucoma, visual fields, parapapillary atrophy, optic nerve